S100A1 deficiency impairs postischemic angiogenesis via compromised proangiogenic endothelial cell function and nitric oxide synthase regulation novelty and significance - Most, Patrick; Lerchenmüller, Carolin; Ritterhoff, Julia; Rohde, David; Busch, Cornelius; Laube, Felix; Heißenberg, Julian; Pleger, Sven Torsten (Circulation research, 2013)
Rationale: Mice lacking the EF-hand Ca2+ sensor S100A1 display endothelial dysfunction because of distorted Ca2+-activated nitric oxide (NO) generation. Objective: To determine the pathophysiological role of S100A1 in endothelial cell (EC) function in experimental ischemic revascularization. Methods and Results: Patients with chronic critical limb ischemia showed almost complete loss of S100A1 expression in hypoxic tissue. Ensuing studies in S100A1 knockout (SKO) mice subjected to femoral artery resection unveiled insufficient perfusion recovery and high rates of autoamputation. Defective in vivo angiogenesis prompted cellular studies in SKO ECs and human ECs, with small interfering RNA-mediated S100A1 knockdown demonstrating impaired in vitro and in vivo proangiogenic properties (proliferation, migration, tube formation) and attenuated vascular endothelial growth factor (VEGF)-stimulated and hypoxia-stimulated endothelial NO synthase (eNOS) activity. Mechanistically, S100A1 deficiency compromised eNOS activity in ECs by interrupted stimulatory S100A1/eNOS interaction and protein kinase C hyperactivation that resulted in inhibitory eNOS phosphorylation and enhanced VEGF receptor-2 degradation with attenuated VEGF signaling. Ischemic SKO tissue recapitulated the same molecular abnormalities with insufficient in vivo NO generation. Unresolved ischemia entailed excessive VEGF accumulation in SKO mice with aggravated VEGF receptor-2 degradation and blunted in vivo signaling through the proangiogenic phosphoinositide-3-kinase/Akt/eNOS cascade. The NO supplementation strategies rescued defective angiogenesis and salvaged limbs in SKO mice after femoral artery resection. Conclusions: Our study shows for the first time downregulation of S100A1 expression in patients with critical limb ischemia and identifies S100A1 as critical for EC function in postnatal ischemic angiogenesis. These findings link its pathological plasticity in critical limb ischemia to impaired neovascularization, prompting further studies to probe the microvascular therapeutic potential of S100A1.